2017
DOI: 10.1186/s10397-017-1018-0
|View full text |Cite
|
Sign up to set email alerts
|

The role of the multidisciplinary team in the management of deep infiltrating endometriosis

Abstract: The multidisciplinary team (MDT) is considered good practice in the management of chronic conditions and is now a well-established part of clinical care in the NHS. There has been a recent drive to have MDTs in the management of women with severe endometriosis requiring complex surgery as a result of recommendations from the European Society for Human Reproduction and Embryology (ESHRE) and British Society for Gynaecological Endoscopy (BSGE). The multidisciplinary approach to the management of patients with en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…15 With respect to MDT meetings running effectively, participants agreed that teamwork and respect was important as it would positively affect patient outcome and help provide a practical approach in delivering quality patient care. 16 Similar studies 12,17 have previously shown that poor interpersonal relationships and absence of teamwork were huge barriers to a successful MDT meeting, placing patient safety at risk and generating situations rife for medical errors. 18 As for key barriers to MDT meetings, it was agreed upon that lack of patient information was an important barrier because it served to inhibit decision making or provide patients with clinically inappropriate decisions.…”
Section: Discussionmentioning
confidence: 89%
“…15 With respect to MDT meetings running effectively, participants agreed that teamwork and respect was important as it would positively affect patient outcome and help provide a practical approach in delivering quality patient care. 16 Similar studies 12,17 have previously shown that poor interpersonal relationships and absence of teamwork were huge barriers to a successful MDT meeting, placing patient safety at risk and generating situations rife for medical errors. 18 As for key barriers to MDT meetings, it was agreed upon that lack of patient information was an important barrier because it served to inhibit decision making or provide patients with clinically inappropriate decisions.…”
Section: Discussionmentioning
confidence: 89%
“…The multidisciplinary team approach is considered as one of the essential practice in the management of chronic conditions. According to a study conducted by Ugwumadu et al [22], MDT is well established in the provision of clinical care in most critical care institutions. More importantly, in recent days there has been a drive to have MDT in the management of women experiencing severe endometriosis and who need complex surgery.…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, in recent days there has been a drive to have MDT in the management of women experiencing severe endometriosis and who need complex surgery. In fact, the European Society for Human Reproduction and Embryology (ESHRE) and the British Society for Gynaecology Endoscopy (BSGE) have advocated for the implementation of the practice [22]. Further, both ESHRE and BSGE argue that the adoption of the multidisciplinary approach will lead to better results in patient care.…”
Section: Discussionmentioning
confidence: 99%
“…First, there is a lack of patient involvement in the discussions, as patients are not present at these meetings, and it must be assured that patient preferences and their social circumstances are taken into account for the most appropriate team decisions. Divergent treatment priorities with a failure to reach a joint recommendation have been commonly reported, as well as poor leadership, insufficient teamwork, time pressures, an absence of key professionals in attendance and the absence of key clinical information; all of which can affect the clinical decision making of MDTs in general 142,143 . MDTs remain a work in progress but continue to add benefit for management during their evolution.…”
Section: [H1] the Pathologists Role In The Mdtmentioning
confidence: 99%